A comprehensive framework for physical evaluation of manual material handling tasks. (7th May 2012) - Parida, Ratri; Ray, Pradip Kumar
While designing a worksystem for manual material handling (MMH) tasks, consideration of physical evaluation is of paramount importance in order to identify and minimise both short-term and long-term risks. In this context, assessment of occupational risk factors associated with the physical environment of a worksystem is a critical research need. In this paper, a generic framework for physical evaluation of MMH tasks is proposed. Four kinds of physical environment may be considered in this approach. This framework has been applied for a typical masonry job in a construction site located in Eastern India particularly with respect to effect of thermal environment. Representative sample of 23 male workers were examined. The metabolic rate among mason workers was calculated to be 602.633 W for an average temperature and humidity of 35.9°C and 55.5% RH, respectively. However, relevant solutions for improvements, such as introduction of rest allowances, etc., were suggested.